Resolution of large aortic valve vegetations in antiphospholipid syndrome treated with therapeutic anticoagulation: a report of two cases and literature review. (December 2018) - Yuriditsky, E; Torres, J; Izmirly, P M; Belmont, H M
Non-bacterial thrombotic endocarditis in antiphospholipid syndrome presents a management dilemma. Large mobile valvular lesions pose an increased risk of stroke and arterial embolization. However, surgical excision or valve replacement in such patients carries high morbidity and mortality, while anticoagulation alone has limited data. We describe two patients with antiphospholipid syndrome presenting with neurologic events and large non-bacterial aortic valve vegetations. Both patients were successfully managed with anticoagulation and demonstrated rapid dissolution of lesions without evidence of recurrent embolic events. We provide a literature review describing additional cases managed with anticoagulation with dissolution of valvular lesions over time. Our cases further support the efficacy and safety of anticoagulation in patients with antiphospholipid syndrome and non-bacterial thrombotic endocarditis in the context of arterial embolization.